Epidemiology of Goat Nematode Infections in Different Ecological Regions of Argentina´S Northwest - Suarez, Victor Humberto; Martinez, Gabriela Marcela; Olmos, Leandro Hipolito (Global Press Hub, 2022)
The aim of this work was to study the etiology and epidemiology of gastrointestinal nematodes (GIN) of goat from the Arid valleys and canyons (AVC), Tempered valleys (TV) and the Semiarid Chaco (SC) regions of northwestern Argentina. Ten flocks were studied and 35 to 40 goats per flock (total= 420 goats) were fecal matter sampled each 30-40 days. Individual eggs per gram of faeces (epg) and faeces cultures were performed. Differences among epg were compared using Kruskal–Wallis non-parametric test. The epg of the three regions showed the same trend: an increment from February reaching the highest average epg peak in April-May and then a fall ​​towards the summer. Goat flocks of TV region showed the highest epg compared to the other two regions, which generally showed low epg values. Haemonchus sp. and Trichostrongylus spp. were the predominant nematode genera recovered in the three regions, although in a smaller proportion Teladorsagia, Oesophagostomum, Nematodirus, Trichuris, Skrjabinema and Strongyloides genera were also recovered. These results show that GIN would be a limiting factor of caprine production in the TV and only during critical periods and under some breeding systems in the other regions.